Not dead yet : the memoir - Collins, Phil (Crown Archetype, 2016)
The Genesis front man and successful solo artist presents a reflective memoir that shares insights into the remarkable experiences behind many of his iconic songs and performances, discussing his early years, relationships with fellow artists, and struggles with addiction.